Media - teatr/spektakl - Gwóźdź, Andrzej (Wydawnictwo Naukowe UAM, 2004)
Considering the nature of the relation medium - form the author proposed an insight into two models of relationships between the cinema and the theatre: the first one including the decade of 1925-1935 and the contemporary one. However, the author is not concerned with how the theatre takes advantage of the achievements of the cinema, but he wishes to show the intermedial relationships which join the stage with the screen at the level of the medium - as a vision machine incorporated into a wide system of culture. And this is connected not only with techniques of forming the presented worlds, but first of all with calculating newer and newer environments for technology of the technically mediated seeing. Thus, if intermedia character was formerly expressed in the exchange of forms between the media (film in the theatre/spectacle in film), then the contemporary spaces of the borderline (represented, let's say, through Peter Greenaway's installations) concern tensions between the materiality of the world, medial character of cinema images and mobility of the spectator. Theatre becomes here an element of film culture, and film intervenes in the stage creating spectacles of medial interfaces.
Media - theatre/spectacle